“A Community of One”: Social Support Networks and Low-income Tenants Living in Market-rental Housing - Leviten-Reid, Catherine; Desjarlais-deKlerk, Kristen (Engaged Scholar Journal, 2024)
Social networks, and the supports they provide, are thought to be key to the survival of those living in poverty. In light of this, we have examined the social support networks of low-income renters living in market housing and who are in receipt of rent subsidies and assistance from housing workers. Our work is rooted in a partnered research initiative on affordable rental housing for those in greatest need. After 21 interviews with tenants and service providers, we found that participants in our study have limited informal social support and that this support is confined to instrumental rather than emotional dimensions. Many of the participants discussed how their housing helped them leave harmful networks and contributed to their decision to cut ties with former acquaintances. However, it is also clear that the individuals in our study were not without ties. Despite having limited, and also actively limiting, informal ties, participants sought and received extensive material and emotional support from non-profit organizations including harm reduction, youth, and women’s centres, and housing workers. Our findings show that these organizations play an important role beyond material survival and suggest the importance of ensuring tenants are able to access these organizations and that non-profit organizations have adequate resources.